IMPROVING THE SYSTEM OF SPIRITUAL AND MORAL-SPIRITUAL TRAINING OF FUTURE TEACHERS - Nurumbekova, Y. (International Journal of Psychosocial Rehabilitation, 2020)
In educational institutions of the world, when training teachers in the educational process, mechanisms have been introduced to ensure the relationship and organic relationship of education and upbringing, to expand the pedagogical and psychological capabilities of spiritual-moral competence. In countries such as the United States, England, Germany, Japan, France, and Russia, special attention is paid to improving the system of spiritual-moral training of future teachers. In higher educational institutions, as part of the improvement of professional pedagogical activity, scientific research is carried out on the formation of spiritual-moral qualities of future teachers, the implementation of the system of their diagnostics, and ensuring organic compliance with spiritual-moral qualities. Scientific research is being carried out to develop ef ective organizational and pedagogical mechanisms for training teachers based on rich national cultural and historical traditions, customs and universal values, and to ensure the priority of humanization of education.